Are psychosocial interventions effective at increasing condom use among Black men? A systematic review. (October 2021) - Nwaosu, Uzochi; Raymond-Williams, Rianna; Meyrick, Jane
Black men experience a disproportionate burden of sexually transmitted infections (STIs) in the United Kingdom (UK). STIs can seriously affect the health and well-being of affected individuals. With condoms effective at preventing STI transmission, this review aims to explore the evidence of effectiveness of psychosocial interventions at increasing condom use among Black men to inform UK-based interventions for this at-risk but unheard population. Nine databases were searched for qualifying studies. Two reviewers independently assessed the quality of studies. A narrative synthesis read across the heterogeneous studies for evidence of effectiveness. A total of 17 studies met the inclusion criteria. This review identified scientifically weak evidence of effectiveness in multifaceted psychosocial interventions to increase condom use among Black men, particularly men who have sex with women and men who have sex with men mainly from United States settings. The multifaceted nature of interventions provides obscure evidence on successful elements of interventions with positive effects. Despite the disproportionate STI burden among this group, no UK-based studies were identified. Future research should aim to better understand condom use behavioural experiences and motivators of condom use among UK Black men to inform ethnically culturally relevant and tailored interventions.